Intercalation and elimination of carbonate ions of NiCo layered double hydroxide for enhanced oxygen evolution catalysis. (28th April 2020) - Wang, Shenggao; Wang, Tao; Wang, Xujie; Deng, Quanrong; Yang, Jingjing; Mao, Yangwu; Wang, Geming
Abstract: The developments of inexpensive and efficient oxygen evolution reaction (OER) electrocatalysts without noble metals are very critical for energy conversion and storage systems. In this work, a series of NiCo-layered double hydroxide (NiCo-LDH) and NiCo oxides using co-precipitation and thermal treatment method have been successfully synthesized. Structural characterizations have been investigated by X-ray powder diffraction (XRD), Field emission scanning electron microscope (FE-SEM) equipped with energy-dispersive X-ray mapping technology (EDS), Transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy respectively (XPS). By intercalating and eliminating CO3 3− anions in the layers of bulk NiCo-layered double hydroxide (NiCo-LDH), the as-present catalyst (NiCo–CH) exhibit remarkable advantages for OER performance, including porous nanostructures, high surface area, high content of Ni 3+ and Co 2+ on the surface and abundant active sites. With these favorable features, NiCo–CH shows a much better OER performance than that of other catalysts and commercial Pt/C, which has a low onset potential (1.51 V), a low overpotential (343 mV at 10mA/cm −2 ) and a small Tafel slope (66mV/dec −1 ). Our work presents an effective strategy to controllably design and synthesize NiCo-LDH electrocatalysts with optimizable OER performances. Highlights: The exchange and elimination process of CO3 2- anions with NO3 − anions in the interlayers of NiCo-LDH has been clearly observed. The OER performance is linked to porous nanostructures, high surface area and high content of Ni 3+ and Co 2+ . The NiCo-CH show overpotential 343 mV@1010 mA cm−2 and Tafel slope of 66 mV·dec−1.